2007
DOI: 10.1016/j.ejvs.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Injury and Dysfunction Following Elective Abdominal Aortic Surgery

Abstract: Kidney injury occurs in most patients undergoing infrarenal aortic surgery, but only 22% develop acute renal dysfunction. Hypotension and low cardiac output are risk factors that could be avoided by optimizing perioperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 25 publications
6
79
1
4
Order By: Relevance
“…5,6 Studies evaluating kidney function in abdominal aorta surgery demonstrated both glomerular (albuminuria) and tubular (increased urinary NAG-creatinine ratio) injury in up to 96% of the subjects, although only 22% had RIFLE-defined acute kidney injury, and a worse short-term (30 days) and long-term (10 years) survival of the AAA (abdominal aortic aneurysm) surgery patients who experienced a temporary AKI, even if their renal function completely recovered. 7,8 The aim of our study was to evaluate the prevalence of AKI, its association with the short-term (within 30-days postoperatively) and long-term (1 year postoperatively) prognosis in a cohort of patients with severe peripheral artery disease (PAD) undergoing surgical procedures of lower extremity revascularization or amputation and the most important comorbidities associated with AKI development.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Studies evaluating kidney function in abdominal aorta surgery demonstrated both glomerular (albuminuria) and tubular (increased urinary NAG-creatinine ratio) injury in up to 96% of the subjects, although only 22% had RIFLE-defined acute kidney injury, and a worse short-term (30 days) and long-term (10 years) survival of the AAA (abdominal aortic aneurysm) surgery patients who experienced a temporary AKI, even if their renal function completely recovered. 7,8 The aim of our study was to evaluate the prevalence of AKI, its association with the short-term (within 30-days postoperatively) and long-term (1 year postoperatively) prognosis in a cohort of patients with severe peripheral artery disease (PAD) undergoing surgical procedures of lower extremity revascularization or amputation and the most important comorbidities associated with AKI development.…”
Section: Introductionmentioning
confidence: 99%
“…Their study, however did not attempt to quantify proteinuria beyond dipstick, nor did they comment on the role of postoperative proteinuria. To our knowledge, only four very small studies (largest, n=69) have commented on the role of postoperative proteinuria as a predictor of AKI (21,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Third, renal failure is an important confounding factor that may limit the predictive role of PCT in the early diagnosis of postoperative infections, also considering the fact that postoperative renal function deterioration is quite frequent after abdominal aortic surgery. 30 Finally, physicians were not blinded to PCT values; therefore, they might have ordered more radiological and microbiological examinations, if PCT was seen to be high. New topics for future researches could be the interpretation of PCT values in relation to the deterioration of renal function, the comparison of PCT curves in patients with different types of postoperative complications (not only infections), and the role of PCT in guiding therapy to prevent postoperative complications in association with other markers.…”
Section: Discussionmentioning
confidence: 99%